Embedded Software Development with C - Qian, Kai. (Springer US, 2009)
Embedded Software Development With C Kai Qian About this textbook: Intelligible presentation of the fundamentals of embedded systems design and development using the C programming language and the 8051 microcontroller. Examines the longevity and relevancy of the 8051 microcontroller for designing embedded systems in present applications. Includes extensive appendices for reference work. Encourages a hands-on, incremental learning approach with comprehensive tutorial materials provided both in textbook and online. Embedded Software Development With C offers both an effectual reference for professionals and researchers, and a valuable learning tool for students by laying the groundwork for a solid foundation in the hardware and software aspects of embedded systems development. Key features include a resource for the fundamentals of embedded systems design and development with an emphasis on software, an exploration of the 8051 microcontroller as it pertains to embedded systems, comprehensive tutorial materials for instructors to provide students with labs of varying lengths and levels of difficulty, and supporting website including all sample codes, software tools and links to additional online references.